Relationship between nutrient and soil loss with respect to land configuration and mulches in ginger (Zingiber officinale) - CHOUDHARY, V K (The Indian Journal of Agricultural Sciences, 2020)
Change in topography and retention of indigenously available biomass as mulch conserves the resources at the site. In high rainfall areas and hilly tract, soil and nutrient loss has paramount importance as these resources directly contribute to the crop yield. Ginger (Zingiber officinale Roscoe) is sensitive to soil and nutrient losses. The present study was conducted during 2011–12 and 2012–13 with three land configurations, viz. broad bed and furrow (BBF), ridge and furrow (R&F) and flatbed (FB) in main plots and four mulches, viz. Imperata cylendrica (IC), pine needle (PN), paddy straw followed by weed biomass (PS) along with no mulch (NM) in sub-plots and replicated thrice in ginger. The adoption of BBF considerably lowered the soil loss by 74.2% resulting in restoration of nitrogen (N), phosphorus (P) and potassium (K) to the tune of 49.7%, 59.3% and 69.1%, respectively, over FB plots. Similarly, placement of PN significantly reduced the soil loss by 92% and saved a considerable amount of N (49.9%), P (49.4%) and K (58.2%) over NM. In the hilly area, leftover crop residues, abundant weed biomass and ample tree leaf litter fall are not utilized commercially; these materials along with alteration in topography can be potentially utilized for the restoration of soil and nutrient for sustainable ginger production.